The Urgency of Pluralism in The Digital World: A Study of Religious Reception on Instagram - Melisa Diah Maharani (Rumah Moderasi Beragama of Syekh Nurjati State Islamic Institute Cirebon, 2022)
The development of the digital technology which has become a part of daily life has been influencing religious activities as well. The fenomena brought a new culture where religious behavior appearing in the digital space is no longer reflected as a personal thing between humans and God, but turns into a free-space to accept the interference of other people's power. Each comes up on behalf of the best Islamic teachings. In this context, both diversity and religiosity should go hand in hand. This research is a literature study by examining various sources related to the theme. The descriptive-analytical approach is applied in this study. The results of the study explain that the digital disruption has a major impact on a person's space of expressions. The Qur'an which has a big role in influencing Muslim’s behaviour, explicitly contains verses concerning the diversity and how to deal with that. Acknowledging the verses of pluralism is an effort to understand the multiculture by realizing the values of tolerance, sympathy and empathy.